Application of rotary microfiltration in debittering process of spent brewer's yeast - Artiwan Shotipruk (2018)
This study concerns the production of yeast extract from spent brewer's yeast using rotary microfiltration as a means to combine debittering and cell debris separation into a single step, without using a toxic alkali wash. The pH of yeast homogenate was found to affect protein yield and bitterness of the product. Rotary filtration of yeast homogenate at various pHs resulted in different percent protein transmissions. These were found to be 5.05%, 9.83%, and 30.83% for pH 5, 6, and 7.5, respectively. The bitterness concentration in the permeate was also found to be higher at higher pHs. Autolysis of the cell homogenate prior to filtration increased protein yield and decreased bitterness considerably. At pH 5.5, the protein transmission was increased to 60% and debittering efficiency was increased from 59% to 86%. The permeate flux and protein productivity could be further increased by increasing the rotational speed, but this resulted in a decrease in debittering efficiency. Thus, the rotational speed should be carefully selected to compromise between the yield and product quality. Furthermore, for the tested rotational speeds of 600 and 1000 rpm, the change in feed flow rate from 11 to 35 L h-1changes the flow behavior from turbulent vortex flow to laminar vortex flow, thus decreasing the flux and protein productivity. © 2005 Elsevier Ltd. All rights reserved.